Is this the end of Public Education in Chile? - Paredes, Ricardo (Estudios de Economía, 2016)
In the period 2000 - 2006, municipal or public schools reduced its enrollmentin 186,000 students (13%) in Chile. Meanwhile, privately subsidized schools,receiving the same type of funding, increased their enrollment in 386,000students (38%). In this paper we distinguish demand factors, associated withparents’ decisions, and supply factors, those associated with owners’ decisions,to explain the change in the education structure en Chile. We found evidencethat the asymmetry in the institutional constraints explain only part of the evolution. Other factors, associated with municipal decisions, which in turn areexplained by the asymmetric financing of different schools, explain the mainpart of the change.